Islam, western materialism and Malaysian muslims’ complex debt behavior: an analysis of the religious experts’ viewpoints - Md. Shariff, Anita; Ariffin, Muhammad Irwan; Mohammed, Mustafa Omar; Mahmood, Rosman (Human Resource Management Academic Research Society (HRMARS), 2023)
Malaysian Muslims household debt level has been persistently increasing despite its overwhelming negative effects. This paper attempts to explain the influence of two dominant conflicting ideologies namely Islam and western materialism on Muslims debt behavior. Semi-structured interviews were carried out with six religious experts including two state muftis from Malaysia. Three out of five hypotheses are supported and five other vital issues have emerged. The findings show Muslims debt behavior turns complex when facing the conflict between religious values and materialistic objectives with materialism supersedes Islamic religiosity. Islamic banking and finance (IBF) successfully dilute the conflicts by offering debt-based Syariah-compliant financing that can fulfil both material aspirations and religious consciousness. Certain traditional Islamic principles are compromised with religious experts taking soft stance concerning their applications. Ambiguities, inconsistencies, misleading information, hasty interpretation of riba’, unrealistic aspirations and unconditional support for IBF are other pressing issues emerged from the interviews. Despite the Muslims’ increasing interest in Islam, there is clear lack of concrete guidance on the matter of debt as far as religious experts’ views are concerned. This paper has important implications for understanding in depth the underlying reasons behind Malaysian Muslims’ complex debt behavior reflected by their growing indebtedness. For future research, a survey among ordinary Muslims should be carried out in order to have a broader understanding of Muslims’ actual debt behavior.